2019
DOI: 10.1515/nleng-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamic Response of an Axially Functionally Graded (AFG) Beam Resting on Nonlinear Elastic Foundation Subjected to Moving Load

Abstract: In recent years, structures made of Functionally Graded materials (FGMs) are used in industries due to the continuously compositional variation of the constituents in FGMs along different directions. In order to develop FGMs, nonlinear vibration analysis to study dynamic behavior is needed. This study proposes nonlinear vibration analysis of a simply supported axially functionally graded (AFG) beam subjected to a moving harmonic load as an Euler-Bernoulli beam utilizing Green’s strain tensor. Axial variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…where u and w are the axial and transverse displacements of any point on the neutral axis, respectively. The Von-Karman's nonlinear strain-displacement relationship based on assumptions of large transverse displacements, moderate rotation, and small strain for straight beams are given by [47][48][49]:…”
Section: Modified Couple Stress Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…where u and w are the axial and transverse displacements of any point on the neutral axis, respectively. The Von-Karman's nonlinear strain-displacement relationship based on assumptions of large transverse displacements, moderate rotation, and small strain for straight beams are given by [47][48][49]:…”
Section: Modified Couple Stress Theorymentioning
confidence: 99%
“…Variation of first and second fundamental frequencies due to system parameters is studied. In [47] nonlinear vibration analysis of a simply supported AFG beam subjected to a moving harmonic load as an Euler-Bernoulli beam utilizing Green's strain tensor. The results indicate that these parameters have a considerable effect on both nonlinear natural frequency and response amplitude [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FG materials have attracted considerable interest from many researchers in structural dynamics and statics, and they have been extensively studied, especially in the last few years. Alimoradzadeh et al [2] proposed the nonlinear vibration analysis of a simply supported axial FG beam subjected to a moving harmonic load and resting on a Winkler-Pasternak nonlinear elastic foundation using Green's strain tensor. An approximate analytical solution for forced nonlinear vibration was obtained using the variational iteration method.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear free vibration of the non‐local bi‐directional graded FG Euler–Bernoulli nanobeams was analysed by Nejad and Hadi [10] using the generalised differential quadrature method (GDQM). Alimoradzadeh et al [11] studied nonlinear vibration analysis of axially functionally graded (AFG) beam Euler–Bernoulli beam subjected to a moving harmonic utilising Green's strain tensor. They investigated the effect of some parameters such as the power index and stiffness coefficients, among others, on the nonlinear natural frequency along with the velocity of the moving harmonic load on the nonlinear dynamic response of (AFG) Euler–Bernoulli, where it is found that these parameters have a considerable effect on both nonlinear natural frequency and response amplitude.…”
Section: Introductionmentioning
confidence: 99%